Systemic Radical Scavenger Treatment of a Mouse Model of Rett Syndrome: Merits and Limitations of the Vitamin E Derivative Trolox - Janc, Oliwia A.; Hüser, Marc A.; Dietrich, Katharina; Kempkes, Belinda; Menzfeld, Christiane; Hülsmann, Swen; Müller, Michael (Frontiers in Cellular Neuroscience, 2016)
Rett syndrome (RTT) is a severe neurodevelopmental disorder typically arising from spontaneous mutations in the X-chromosomal methyl-CpG binding protein 2 (MECP2) gene. The almost exclusively female Rett patients show an apparently normal development during their first 6-18 months of life. Subsequently, cognitive- and motor-impairment, hand stereotypies, loss of learned skills, epilepsy, and irregular breathing manifest. Early mitochondrial impairment and oxidative challenge are considered to facilitate disease progression. Along this line, we recently confirmed in vitro that acute treatment with the vitamin E-derivative Trolox dampens neuronal hyperexcitability, reinstates synaptic plasticity, ameliorates cellular redox balance, and improves hypoxia tolerance in male MeCP2-deficient (Mecp2-/y) mouse hippocampus. Pursuing these promising findings, we performed a preclinical study to define the merit of systemic Trolox administration. Blinded, placebo-controlled in vivo treatment of male mice started at postnatal day 10-11 and continued for ~40 days. Compounds (vehicle only, 10 mg/kg or 40 mg/kg Trolox) were injected intraperitoneally every 48h. Detailed phenotyping revealed that in Mecp2-/y mice, blood glucose levels, lipid peroxidation, synaptic short-term plasticity, hypoxia tolerance, and certain forms of environmental exploration were improved by Trolox. Yet, body weight and size, motor function, and the rate and regularity of breathing did not improve. In conclusion, in vivo Trolox treatment partially ameliorated a subset of symptoms of the complex Rett phenotype, thereby confirming a partial merit of the vitamin E-derivative based pharmacotherapy. Yet, it also became evident that frequent animal handling and the route of drug administration are critical issues to be optimized in future trials.